Effectiveness of health facility governing committees in Tanzania: A case study of Musoma district council - Pancras, Vedastus (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management in partial fulfillment of the requirements for award of the degree of Master in Public Administration (MPA) of Mzumbe University